2019
DOI: 10.1021/acsomega.9b02321
|View full text |Cite
|
Sign up to set email alerts
|

Uniformly Decorated Molybdenum Carbide/Nitride Nanostructures on Biomass Templates for Hydrogen Evolution Reaction Applications

Abstract: Natural fibrils derived from biomass were used as a template to synthesize uniformly decorated nanoparticles (10–12 nm) of molybdenum carbide (Mo 2 C) and molybdenum nitride (Mo 2 N) supported on carbon. The nanoparticles have been synthesized through the carburization and nitridation of molybdenum on cotton fibrils, using a high-temperature solid-state reaction. The catalyst exhibits an onset potential of 110 mV and an overpotential of 167 mV to derive a cathodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…13,14 For instance, Gong et al 15 reported the synthesis of the MoN/ultrathin twodimensional (2D) g-C 3 N 4 composite, which is a hybrid composite to be used as electrode materials for visible light photocatalytic H 2 evolution using the boil bathing method. Mo 2 N was also developed by Kumar et al 16 durability in acidic media. Several carbon-based materials such as graphene oxide (GO), 17 carbon nanofibers (CNFs), 18 carbon nanotubes (CNTs), 19 ordered mesoporous carbon (OMC), 20 and graphitic carbon nitride (GCN) 21 have been used for electrochemical sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 For instance, Gong et al 15 reported the synthesis of the MoN/ultrathin twodimensional (2D) g-C 3 N 4 composite, which is a hybrid composite to be used as electrode materials for visible light photocatalytic H 2 evolution using the boil bathing method. Mo 2 N was also developed by Kumar et al 16 durability in acidic media. Several carbon-based materials such as graphene oxide (GO), 17 carbon nanofibers (CNFs), 18 carbon nanotubes (CNTs), 19 ordered mesoporous carbon (OMC), 20 and graphitic carbon nitride (GCN) 21 have been used for electrochemical sensors.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Recently, molybdenum nitride (MoN) has shown increasing attention for applications in electrochemical energy storage and photocatalytic and enhanced electrocatalytic reactions. It is a research hotspot currently, owing to its low electrical resistance, high conductivity, superior corrosion resistance stability, and excellent mechanical properties. , For instance, Gong et al reported the synthesis of the MoN/ultrathin two-dimensional (2D) g-C 3 N 4 composite, which is a hybrid composite to be used as electrode materials for visible light photocatalytic H 2 evolution using the boil bathing method. Mo 2 N was also developed by Kumar et al from natural fibrils derived from the biomass template for the application in HER. The catalyst exhibited excellent H 2 production with long-term durability in acidic media.…”
Section: Introductionmentioning
confidence: 99%
“…Figure 6a represents the XPS survey spectra of the MoO 2 /N-doped-carbon nanocomposite, where five prominent binding energy peaks at 235.08 eV (Mo 3d), 285.08 eV (C 1s), 398.08 eV (N 1s), 416.08 eV (Mo 3p 1/2 ), and 531.08 eV (O 1s) were observed. 56,57 The deconvoluted Mo 3d spectra (Figure 6b) consisted of six peaks. The binding energies of 231.0 and 234.11 eV were assigned to Mo 4+ , whereas the binding energies of 232.44 and 235.58 eV clarified the presence of Mo 6+ in the MoO 2 /Ndoped-carbon nanocomposite.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The chemical valence and coordination states of the elements present in the MoO 2 /N-doped-carbon nanocomposite were analyzed through XPS. Figure a represents the XPS survey spectra of the MoO 2 /N-doped-carbon nanocomposite, where five prominent binding energy peaks at 235.08 eV (Mo 3d), 285.08 eV (C 1s), 398.08 eV (N 1s), 416.08 eV (Mo 3p 1/2 ), and 531.08 eV (O 1s) were observed. , The deconvoluted Mo 3d spectra (Figure b) consisted of six peaks. The binding energies of 231.0 and 234.11 eV were assigned to Mo 4+ , whereas the binding energies of 232.44 and 235.58 eV clarified the presence of Mo 6+ in the MoO 2 /N-doped-carbon nanocomposite. ,,, Since MoO 2 is a metastable phase, the presence of Mo 6+ was commonly observed in MoO 2 /carbon NMs because of the surface oxidation of MoO 2 by air. ,,, Besides the presence of Mo 4+ and Mo 6+ , two additional peaks of Mo 3d appear at 230.0 and 233.04 eV, which were generally correlated to the Mo–N bond .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation